Green synthesis of silver nanoparticles using Saudi Xanthium strumarium extract: anticancer potential against breast and lung cancer cells - Aati, Hanan; Al-Qahtani, Jawaher; Al-Taweel, Areej; Farshori, Nida N.; Orfali, Raha; Perveen, Shagufta (Frontiers in Pharmacology, 2025)
IntroductionThis study reports Xanthium strumarium aqueous extract-mediated synthesis of silver nanoparticles and mechanistic evaluation of their antiproliferative effects against breast (MCF-7) and lung (A-549) cancer cells.MethodsThe synthesized XT-AgNPs were analyzed in terms of their size, structure, shape, and morphology using various analytical techniques. UV/Vis spectroscopy revealed a distinct peak at 447 nm, indicating the successful synthesis of AgNPs. SEM/EDX and TEM analyses confirmed that the XT-AgNPs had spherical shape and exhibited a uniform size distribution. XRD analysis verified that XT-AgNPs exhibited a face-centered cubic (FCC) crystalline structure, with a calculated crystalline size of 27.90 nm. Additionally, the cytotoxic potential of XT-AgNPs were examined on MCF-7 and A-549 cancer cells using MTT and NRU assays. Cell death was assessed through morphological analysis, while the reactive oxygen species generation was evaluated using DCFH-DA dye.Results and DiscussionXT-AgNPs demonstrated notable cytotoxic effects on MCF-7 and A-549 cells with IC50 values of 44.3 and 57.4 μg/mL, respectively. Morphological and DCFH-DA analyses revealed the effect of XT-AgNPs in reducing the cell proliferation and inducing ROS generation. GC/MS analysis was conducted to identify the phytochemicals present in the extract which showed 29 peaks of phytoconstituents. These 27 phytoconstituents were further analyzed by in silico studies, molecular docking study was carried out for all phytoconstituents, and compounds having maximum binding affinity were analyzed for their ADMET profile. Overall, the results highlight the anticancer properties of XT-AgNPs, indicating their potential as an effective agent in human breast and lung cancer management.